2017
DOI: 10.3892/ol.2017.7680
|View full text |Cite
|
Sign up to set email alerts
|

Molecular challenges of neuroendocrine tumors (Review)

Abstract: Abstract. Neuroendocrine tumors (NETs) are a very heterogeneous group that are thought to originate from the cells of the endocrine and nervous systems. These tumors develop in a number of organs, predominantly in the gastrointestinal and pulmonary systems. Clinical detection and diagnosis are reliable at the late stages when metastatic spread has occurred. However, traditional conventional therapies such as radiation and chemotherapy are not effective. In the majority of cases even surgical resection at that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 151 publications
0
17
0
Order By: Relevance
“…TP53 mutations have been reported in approximately 80% of poorly differentiated neuroendocrine cancers [13] . As part of the PI3K-AKT-mTOR pathway, PI3KCA is considered to be a molecular target for the treatments of advanced NET [14] . Kwon et al rst reported a case combined hepatocellular carcinoma and neuroendocrine carcinoma with ectopic secretion of parathyroid hormone.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 mutations have been reported in approximately 80% of poorly differentiated neuroendocrine cancers [13] . As part of the PI3K-AKT-mTOR pathway, PI3KCA is considered to be a molecular target for the treatments of advanced NET [14] . Kwon et al rst reported a case combined hepatocellular carcinoma and neuroendocrine carcinoma with ectopic secretion of parathyroid hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Histone methylation of genes encoding other CDKis, such as p16 Ink4a (CDKN2A) and p14 ARF , has been identified as an early driver in NET pathogenesis. Enhanced H3K9me3 activity through menin-Daxx interactions leads to epigenetic inhibition of a pro-proliferative gene, Mme, and results in NET suppression in mice (Patel et al 2018), while Men1 −/− mouse embryonic fibroblasts have reduced global methylation of histone H3K9 and H3K4. In addition, menin interacts with the SUV39H1 (suppressor of variegation 3-9 homolog protein family) and mediates H3K9 methylation.…”
Section: Histone Modification (Acetylation and Methylation)mentioning
confidence: 99%
“…Neuroendocrine neoplasms are genomically and clinically heterogeneous. This heterogeneity occurs between cancers originating from different organs, within the cancers originating in the same organ, and between primary and metastatic lesions [4,[11][12][13]. For instance, small intestine NETs are genomic stable cancers, with a low mutational load compared with NETs originating from different organs, such as lung and pancreas.…”
Section: Neuroendocrine Neoplasms and Molecular Heterogeneitymentioning
confidence: 99%
“…Neuroendocrine neoplasms (NENs) are originated from the neoplastic transformation of neuroendocrine cells at various anatomic locations, being the gastrointestinal tract, the endocrine pancreas and the respiratory tract, the most involved sites. [4].…”
Section: Introductionmentioning
confidence: 99%